Grassland management and coenology investigations in the sheep pasture near Mezőszilas (Mezőföld) - Penksza, Károly; Wagenhoffer, Zsombor; Nagy, Beatrix; Szentes, Szilárd; Bajnok, Márta; Bodnár, Ákos; Fűrész, Attila (Animal welfare, Ethology and Housing Systems (AWETH), 2023)
We examined the vegetation of the sheep pasture in Mezőföld, on the border of Mezőszilas, from the point of view of nature conservation and grassland management. Three groups of vegetation types were separated in the area. The lower-lying area is marshy, with patches of loess grass on the slopes and uncharacteristic types of dry grassland vegetation. The patches of cooler areas with deeper slopes, in which the dominant species are Agrostis stolonifera, Festuca arundinacea and Lolium perenne are the most suitable for grazing. The giant individuals of Juncus infexus are unfit for grazing, their removal is justified. We found tall stands of Carex riparia and Carex acutiformis on the deepest surface of the area, which was under water for the longest time. The first one was dry grassland with no characteristic closed grassland on the ridge of the area (A), where the Festuca rupicola can be found among the loess grassland elements. The second area was the part of the slope where almost only annual grasses, primarily Bromus tectorum (B): It turns green in the fall, but the proportion of perennial species in the area is very small, the area almost looks like an abandoned field. The third is situated at the bottom of the valley (C). The dominant species in this is Poa angustifolia, but Poa humilis also occurs, as well as Lolium perenne and Agrostis tenuis, which are very important from a lawn management point of view. On the steep slopes of the area, there are stands of degenerate loess grass, but they also contain protected species. Among them are the Astragalus asper, which is common in sandy grassland, and the Taraxacum serotinum, which is also a characteristic species of loess area. Grazing the area with sheep has kept the vegetation of the area valuable both from the point of view of nature conservation and grassland management. Bromus tectorum is the dominant species of featureless dry lawn found on the dry southern slope of the site. Nutrient supplementation is recommended. The research was supported by the AKGF-119-1-202 project.